METHODS FOR ASSESSING THE GENERAL PSYCHOLOGICAL STATE OF ATHLETES BEFORE COMPETITIONS - Abduvohid, Mamadiyorov (Research Focus International Scientific Journal, 2026)
This article analyzes the methods for assessing the general psychological state of athletes before competitions from both theoretical and practical perspectives. It highlights psychodiagnostic techniques used to evaluate psychological readiness, stress resistance, motivation, and emotional stability. Furthermore, it presents approaches to optimizing the training process based on diagnostic results in order to improve athletic performance.